Study of incidence and clinical presentation of tubercular abdominal emergencies - Kumar, Mahendra (International Surgery Journal, 2020)
Background: Tuberculosis is a common surgical problem in our community. Emergency surgery is usually required and surgical procedure depends upon the location and extent of the disease. Objective of the study was to determine the incidence of abdominal emergencies due to tuberculosis. Methods: This observational study involved 300 patients with abdominal tuberculosis admitted either as a case of acute of subacute abdominal emergencies and tract in Lal Lajpath Rai hospital Kanpur, Uttar Pradesh, India, and associated hospitals. Data was entered into Excel worksheet and analyzed using SPSS version 16.0. Detailed data of each patient was entered on a Microsoft excel. Data were presented in number and percentages. Results: The maximum number of cases were in third decade of life, age group 21-30. There were 120 males and 180 females. Male to female ratio was 1:1.5. Most of cases not having evidence of tuberculosis. History of pulmonary tuberculosis and abdominal tuberculosis were observed in 25% and 13% of the total cases. Abdominal pain was the commonest symptoms. Generalized pain was present in 136 cases and localized pain was present in 154 cases. 186 cases were presented as subacute intestinal obstruction and 114 cases patients were presented as acute abdomen. Conclusions: Acute abdominal condition is one of the most frequent emergencies, early diagnosis with prompt treatment is essential for a promising prognosis.